2018
DOI: 10.1111/odi.12923
|View full text |Cite
|
Sign up to set email alerts
|

Bone regeneration by freeze‐dried composite of octacalcium phosphate collagen and teriparatide

Abstract: Objective Octacalcium phosphate (OCP) and collagen (col) composite (OCPcol) demonstrated superior bone regeneration properties, and its commercialization appears to be forthcoming. As a practical medical material for new combination products, we developed a freeze‐dried composite with OCPcol and teriparatide (TPTD) (OCPcolTPTDf), and investigated its bone regenerative properties. Materials and Methods A disk of OCPcol was made by mixing OCP granules and atelocollagen for medical use. Then, OCPcolTPTDf was prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The procedure for the implantation of OCP/Col and β‐TCP/Col disks has been previously described (Iwai et al, ; Kamakura et al, ). The experimental animals were anesthetized intraperitoneally with 0.15 mg/kg dexmedetomidine hydrochloride (Domitor) (Nippon Zenyaku Kogyo Co., Ltd., Koriyama, Fukushima, Japan), 2.5 mg/kg butorphanol tartrate (Vetorphale) (Meiji Seika Pharma Co., Tokyo, Japan), and 2 mg/kg midazolam (Dormicum) (Astellas Pharma, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The procedure for the implantation of OCP/Col and β‐TCP/Col disks has been previously described (Iwai et al, ; Kamakura et al, ). The experimental animals were anesthetized intraperitoneally with 0.15 mg/kg dexmedetomidine hydrochloride (Domitor) (Nippon Zenyaku Kogyo Co., Ltd., Koriyama, Fukushima, Japan), 2.5 mg/kg butorphanol tartrate (Vetorphale) (Meiji Seika Pharma Co., Tokyo, Japan), and 2 mg/kg midazolam (Dormicum) (Astellas Pharma, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Teriparatide may enhance periodontal healing as demonstrated by higher number of PCNA-and VEGF-positive cells, and increased osterix expression, thus promoting PDL cell proliferation, angiogenesis, and osteoblast differentiation (Yoshida et al, 2019). Even local delivery thorough disks containing teriparatide solution seems to have similar effects, suggesting that this route of administration is effective while reducing the risk of potential systemic side effects (Iwai et al, 2018;Kajii et al, 2018). However, it should be highlighted that dosing regimens of teriparatide used in animal studies are quite heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…Considering local application of teriparatide (1.0 or 0.1 µg), Kajii et al (2018) found that local drip of this drug into rat calvarial defects treated with OCP and collagen composite, led to a significantly higher percentage of newly formed bone, independently from teriparatide dosage. Similarly, Iwai et al (2018) showed that adding teriparatide (1.0 or 0.1 µg) in disks composed by OCP or β-TCP with collagen, significantly enhanced bone healing of critical size defects in rat calvaria. Marques et al (2009) investigated the effects of systemic intermittent administration of teriparatide (40 µg/kg daily) on periodontal tissues in rats with ligature-induced experimental periodontitis.…”
Section: Teriparatidementioning
confidence: 91%
See 1 more Smart Citation
“… 28 , 29 Recently, it was reported that OCPcol with a local single administration of TPTD (1 or 0.1 μg), which is a relatively low dose similar to that for the treatment for osteoporosis, enhanced bone repair of a critical-sized bone defect. 30 , 31 Hence, the present study investigated whether single-dose local administration of TPTD with OCPcol achieved bone reconstruction if implanted into a canine segmental mandibular bone defect.…”
Section: Introductionmentioning
confidence: 99%